ANALISIS FAKTOR YANG MEMPENGARUHI MOTIVASI BELAJAR DENGAN INDEKS PRESTASI KUMULATIF MAHASISWA FISIOTERAPI STIKes SITI HAJAR MEDAN TAHUN 2018 - Marya Ningsih (Jurnal Gentle Birth, 2019)
The role of motivation is very important in the activities of student teaching and learning activities. The success of students in completing the curriculum is marked by academic achievement achieved, indicated by the Grade Point Average (GPA). Of the 10 students of the 2016 Siti Hajar Medan STIKes students, the second semester GPA consists of students 1, 3, 4, 5, and 6 above the standard GPA, and students 2, 7, 8, 9 and 10 GPAs are below the standard, which is below 2, 75 allegedly due to learning motivation is still low. This study aims to analyze the factors that influence learning motivation with the cumulative grade point of Physiotherapy students at STIKes Siti Hajar Medan Force 2016.           This study uses a type of survey research with a cross sectional approach. The population was Physiotherapy students who were active in college, namely 97 people. The sample is a student having an IKP below 00 3.00 as many as 60 with a simple random sampling technique. Data collection using a questionnaire. Data analysis consisted of univariate and bivariate with product moment correlation test at 95% significance level.           The results showed that students had a high enough motivation of 43.3% and an average grade point average of 2.6 so that learning motivation needed to be increased to be even stronger. There is a positive and significant relationship between learning motivation and student GPA including a strong category with rxy 0.568. The contribution of learning motivation affects the GPA of 32.2%.           There is a correlation between learning motivation and student's Physiotherapy GPA in 2016. It is recommended to STIKES Siti Hajar Medan Educational Institutions to provide motivation to students, so students can be active and diligent in participating in academic activities through continuous lecturer guidance to students, especially unsatisfactory GPA, availability of books in a complete library and a comfortable and calm atmosphere of the learning environment.           The output plan of this study is scientific publications in national journals (ISSN). Then the Abdominal Streching Exercise and Warm Compress Module in dealing with menstrual pain.  Keywords     :  Motivation, Grade Point Average